GLP-2 Is Locally Produced From Human Islets and Balances Inflammation Through an Inter-Islet-Immune Cell Crosstalk - He, Wei; Rebello, Osmond D.; Henne, Antonia; Nikolka, Fabian; Klein, Thomas; Maedler, Kathrin (Frontiers in Endocrinology, 2021)
Glucagon-like peptide-1 (GLP-1) shows robust protective effects on β-cell survival and function and GLP-1 based therapies are successfully applied for type-2 diabetes (T2D) and obesity. Another cleavage product of pro-glucagon, Glucagon-like peptide-2 (GLP-2; both GLP-1 and GLP-2 are inactivated by DPP-4) has received little attention in its action inside pancreatic islets. In this study, we investigated GLP-2 production, GLP-2 receptor (GLP-2R) expression and the effect of GLP-2R activation in human islets. Isolated human islets from non-diabetic donors were exposed to diabetogenic conditions: high glucose, palmitate, cytokine mix (IL-1β/IFN-γ) or Lipopolysaccharide (LPS) in the presence or absence of the DPP4-inhibitor linagliptin, the TLR4 inhibitor TAK-242, the GLP-2R agonist teduglutide and/or its antagonist GLP-2(3-33). Human islets under control conditions secreted active GLP-2 (full-length, non-cleaved by DPP4) into the culture media, which was increased by combined high glucose/palmitate, the cytokine mix and LPS and highly potentiated by linagliptin. Low but reproducible GLP-2R mRNA expression was found in all analyzed human islet isolations from 10 donors, which was reduced by pro-inflammatory stimuli: the cytokine mix and LPS. GLP-2R activation by teduglutide neither affected acute or glucose stimulated insulin secretion nor insulin content. Also, teduglutide had no effect on high glucose/palmitate- or LPS-induced dysfunction in cultured human islets but dampened LPS-induced macrophage-dependent IL1B and IL10 expression, while its antagonist GLP-2(3-33) abolished such reduction. In contrast, the expression of islet macrophage-independent cytokines IL6, IL8 and TNF was not affected by teduglutide. Medium conditioned by teduglutide-exposed human islets attenuated M1-like polarization of human monocyte-derived macrophages, evidenced by a lower mRNA expression of pro-inflammatory cytokines, compared to vehicle treated islets, and a reduced production of itaconate and succinate, marker metabolites of pro-inflammatory macrophages. Our results reveal intra-islet production of GLP-2 and GLP-2R expression in human islets. Despite no impact on β-cell function, local GLP-2R activation reduced islet inflammation which might be mediated by a crosstalk between endocrine cells and macrophages.